Construction of a ceRNA Network and Analysis of Tumor Immune Infiltration in Pancreatic Adenocarcinoma - Xiao, Jingjing; Lv, Chao; Xiao, Chuan; Ma, Jinyu; Liao, Jun; Liu, Tao; Du, Jun; Zuo, Shi; Li, Haiyang; Gu, Huajian (Frontiers in Molecular Biosciences, 2021)
Pancreatic adenocarcinoma (PAAD) is highly malignant, easy to metastasize, and relapse with an unfavorable prognosis. This study was designed to construct a model of tumor-infiltrating immune cells, a competing endogenous RNA (ceRNA) network related to the prognosis of pancreatic cancer, and to analyze the sensitivity and immunotherapy of pancreatic cancer based on chemotherapeutic drugs on the risk model constructed by ceRNA network.Gene expression profiles and clinical information of PAAD were downloaded from The Cancer Genome Atlas (TCGA) and divided into tumor groups and regular counterparts. Then the CIBERSORT algorithm was used to study the infiltration levels of 22 immune cell subpopulations in pancreatic cancer tissues to screen out prognostically relevant tumor-infiltrating immune cells in PAAD to construct a prognostic model and to build another predictive survival nomogram.Our research identified five critical genes associated with pancreatic cancer survival and three immune infiltration cells (ICI) related to survival in the ceRNA network were screened out, and two survival risk models and nomograms were constructed, and the model efficacy and advantages were assessed with multi-time-point multi-index AUC curves, DCA decision curves, and calibration curves, respectively. Co-expression analysis showed that the genes in the models were significantly correlated with immune cells, and the expression of critical genes was verified consistently at tissue and cellular levels. Patients with low-risk scores of crucial genes in the ceRNA network responded significantly to anti-programmed death-1 (PD-1) treatment, and they showed greater sensitivity to chemotherapeutic drugs such as Docetaxel, Lapatinib, and Paclitaxel, with significant differences in the expression of immune checkpoints in the high and low-risk groups.In this study, it was found that among Competing endogenous RNAs (ceRNAs) (LRRC1, MIR600HG, RNF166) and tumor-infiltrating immune cells (T cells CD8, Macrophages M1) may be related to the prognosis of PAAD. The prognostic model, nomogram, and drug analysis may provide a certain reference value for pancreatic cancer patients' management in the clinic.